Increasing cropping intensity of Fallow-Boro-T. Aman cropping pattern with inclusion of Mustard in Tista Mender Floodplain soil - Khatun, MUS; Ferdous, Z; Haque, Z; Alam, MAU; Hasan, M; Islam, MK (Progressive Agriculture, 2020)
The field experiment was conducted at MLT site Pirgon, Rangpur and Domar, Nilphamari for two consecutive years 2015-17 to introduce BARI Sarisha-14 in the fallow period and to study the comparative agronomic performance and economic return of two cropping sequences (viz. improved cropping pattern-Mustard-Boro rice-T. aman rice and existing cropping pattern -Fallow-Boro rice-T. aman rice) for increasing cropping intensity, productivity and land use efficiency. The experiment was laid out in randomized complete block design with six dispersed replications. Two years mean data showed that the improved management practices for the pattern provided significantly higher yield in improved pattern. Higher rice equivalent yield (REY) of cropping system (mean value 14.49 t ha-1) was recorded with the improved pattern over existing pattern at MLT site Pirganj. REY increased 4.60 t ha-1by inclusion of mustard with improved production technologies for the component crops. Similar results were also found in Domar. The gross return of the improved pattern was BDT.239091 ha-1 which was more than 46.44% higher than farmers’ pattern of BDT.163267 ha-1 at MLT site Pirganj and in Domar gross return of the improved pattern was BDT.241345 ha-1 which was more than 44.18% higher than farmers’ pattern of BDT.167392 ha-1.The gross margin was higher in improved cropping pattern in both locations than existing pattern due to addition of Mustard. Progressive Agriculture 30 (4): 360-370, 2019